The troubled relationship of the emerging powers and the effective development cooperation agenda: history, challenges and opportunities - Gerardo Bracho (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The Development Assistance Committee, the OECD's club of Western donors, promoted the creation of a Global Partnership for Effective Development Cooperation” (GPEDC) in 2011 at a High Level Meeting in Busan, Korea. It was widely considered at the time that the success of the venture (in terms of both inclusiveness and relevance) in large measure hinged on the last-minute decision of China, India and Brazil to join the Partnership as providers of South-South Cooperation (SSC): a modest step forward in the much broader geopolitical effort to accommodate these emerging powers in the post-war liberal order. Only a few years later, however, all three countries had left the GPEDC. This paper explores how they joined, why they left and suggests how they could return. The paper has three sections. The first gives a historical account of the troubled relations between the effectiveness agenda and the “providers of SSC” from its origins to the present. The second section tackles the crucial question of why the emerging powers left the GPEDC. Although a number of factors led to this decision, the paper concludes that the main one was the issue of their “identity” and the (donor) responsibilities that this implied. Drawing on a simple “burden-sharing” model with three actors (donors, Southern providers and recipients), this section seeks to understand why cooperation broke down at the GPEDC. It points to a lack of trust and open communication among donors and emerging powers and an inability on the part of the recipient countries to broker a deal that would keep the Partnership together. Finally, the third section offers recommendations in historical context on what to do to revitalise the GPEDC and bring the emerging powers back in. It advocates for a GDPEC that is focussed on an agenda of commitments rather than one of mere dialogue. Nevertheless, it recognises that the context has changed considerably in the four years since the emerging powers left the Partnership. The paper, therefore, recommends re-engaging them on the basis of “self-differentiated” commitments, the “new” burden-sharing formula that helped to seal the recent Paris climate change agreement. Given the ambitious nature of the Sustainable Development Goals, it is vitally important to ensure greater cooperation and stricter commitments from all actors. To achieve this, a strong GPEDC is crucial.
Keywords: 330; Aufstrebende Mächte; Regionale + globale + transnationale Governance